UTILIZATION OF ULTRASONIC WAVE IN THE PRODUCTION OF REDUCED GRAPHENE OXIDE FROM COCONUT SHELL BIOMASS: ECO-FRIENDLY AND SUSTAINABLE APPROACH - Zen, Nur Afifah; Permatasari, Indah; Hikmah, Irmayatul; Yuliantoro, Prasetyo; Rahmawati, Dina (Universitas Mataram, 2025)
The production of reduced graphene oxide (rGO) using environmentally friendly methods remains a challenge in the development of sustainable energy storage materials.Â This study explores the utilization of ultrasonic waves in the production of rGO from coconut shell biomass as a green and cost-effective approach. Ultrasonic treatment for 30 minutes (UB-30) resulted in a graphene sheet morphology, enhanced carbon content, and reduced oxygen functional groups on rGO. Electrochemical characterization showed that the specific capacitance of the ultrasonically treated rGO (UB-30) reached 789 F/g at a scan rate of 10 mV/s, demonstrating competitive electrochemical performance for supercapacitor applications. The use of coconut shell biomass as a precursor offers an eco-friendly solution, while the application of ultrasonication enables higher production efficiency with lower energy consumption. These findings contribute significantly to the development of electrode materials for supercapacitors and sustainable energy storage systems.